1979
DOI: 10.1002/crat.19790140313
|View full text |Cite
|
Sign up to set email alerts
|

Glas Natur, Struktur und Eigenschaften

Abstract: Dieses Werk ist urheberrechtlich geschützt. Die dadurch begründeten Rechte, insbesondere die der Übersetzung, des Nachdrucks, des Vortrags, der Entnahme von Abbildungen und Tabellen, der Funksendung, der Mikroverfilmung oder der Vervielfältigung auf anderen Wegen und der Speicherung in Datenverarbeitungsanlagen, bleiben, auch bei nur auszugsweiser Verwertung, vorbehalten. Eine Vervielfältigung dieses Werkes oder von Teilen dieses Werkes ist auch im Einzelfall nur in den Grenzen der gesetzlichen Bestimmungen de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Iron: Fe in its trivalent state can be responsible for the yellow-brown colour of glass (Scholze 1988;Kurzmann 2003). In the translucent yellow-brown parts of fragments 2 and 29, no colouring agents except Fe were detected.…”
Section: Ionic Colouring Agentsmentioning
confidence: 99%
“…Iron: Fe in its trivalent state can be responsible for the yellow-brown colour of glass (Scholze 1988;Kurzmann 2003). In the translucent yellow-brown parts of fragments 2 and 29, no colouring agents except Fe were detected.…”
Section: Ionic Colouring Agentsmentioning
confidence: 99%
“…Thus, intensive dusting with B 4 C triggered crystallization of needle-like foreign crystals and caused a rippled surface morphology. These e¬ects can be explained assuming an enrichment of B 2 O 3 in the near-surface area due to oxidation of B 4 C and to the well-known decrease in surface tension by the addition of B 2 O 3 (Scholze 1977). This observation is con rmed by the chemical inertness of B 4 C under vacuum.…”
Section: (F ) Solid Particlesmentioning
confidence: 99%
“…In a different but equally important context, the rich diversity of phosphate mineralogy is matched by a large glassforming range of composition in silicophosphate and phosphate glasses (Scholze, 1988), and indeed P2O5 itself is glassforming. As a result the properties of phosphate glasses and liquids have been investigated (Bansal & Doremus, 1986 The structural role of phosphorus in silicate melts has been the subject of a large number of spectroscopic measurements (see Mysen, 1988, for a review) and it has been demonstrated that phosphorus additions can produce octahedrally coordinated Si in silicophosphate glasses at 1 atm (Sekiya et al, 1988).…”
Section: Introductionmentioning
confidence: 99%